STRATEGY OF VEGETABLE TRADERS AT ARENGKA MORNING MARKET IN PEKANBARU CITY - Jepri Juliansyah (Yayasan Wayan Marwan Pulungan, 2025)
This research was conducted at the Arengka Morning Market, Pekanbaru City. Arengka Morning Market Pekanbaru City is one of the traditional markets in Pekanbaru, Riau, precisely in East Sidomulyo, Marpoyan Damai District. It is very strategically located in the middle of the city of Pekanbaru. The purpose of this research is to find out the activities of vegetable traders at the Arengka Morning Market, Pekanbaru City, to find out the competitive activities of vegetable traders at the Arengka Morning Market, Pekanbaru City, and to find out the competitive activities between vegetable traders at the Arengka Morning Market, Pekanbaru City. The type in this study is qualitative research. The theory used in this study is the Cravens competition. The results of this study are to find out the activities of vegetable traders in the Arengka Morning Market and the strategy of vegetable traders in the Arengka Morning Market. Vegetable traders have a strategy for selling vegetables, namely a strategy to get merchandise in the form of vegetables, then a strategy to reach customers, and a strategy to determine prices.